Acquiring new customers by price comparison sites vs. direct marketing: Long-term effects on customer loyalty and cross-buying in a contractual setting - Musiol, Andreas; Steul-Fischer, Martina (2020)

Customer Behavior in the Insurance Industry: Insights from Usage-based Car Insurance, Customer Referral programs, and Price Comparison Sites - Musiol, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)

Customer Referral Programs: How Demographic Similarity, Risk Profile of the Product, and Referral Channels Influence Referral Success - Musiol, Andreas; Steul-Fischer, Martina; Pescher, Christian (NA – Advances in Consumer Research, 2019)

Der Einfluss der Produktart und des Weiterempfehlungskanals auf den Erfolg von Weiterempfehlungen bei Versicherungen - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2019)
For many insurance providers referral programs are a promising customer acquisition tool. Previous research work has been widely studied successful referrals, thereby neglecting unsuccessful referrals. In an empirical study, we examine potential drivers of successful referral likelihood. In particular, we analyze the impact of tie strength (weak ties vs. strong ties) and referral channels (personal vs. written) on the likelihood of successful referrals, and the moderating role of product type (life insurance vs. non-life insurance). Based on customer data from an insurance provider, we show that the likelihood of successful referrals substantially depends on strong social ties (i.e., both the referring and the referred person are living in the same household). Further, a positive interaction effect between tie strength and product type reveals that successful referral likelihood is not merely a result of tie strength: Strong-tie (weak-tie) referrals yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances. Finally, we show that successful referral likelihood also depends on the choice of the referral channel. Referrals that are mentioned across verbal (written) referral channels yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances.
CRIS-Team Scopus Importer:2019-07-09

Digitalisierte Beratungsunterstützung im Versicherungsvertrieb - Musiol, Andreas; Steul-Fischer, Martina; Gatzert, Nadine (Versicherungsvermittlung, 2018)

Price framing and consumers´purchase intention on pay-how-you-drive tariffs - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2019)
Pay-how-you-drive (PHYD) is an innovative car insurance tariff offered by insurance companies, whereby prices are based on an individual’s driving style and mileage. In an experimental study, we analyze the effect of price framing on purchase intention for PHYD tariffs. Results demonstrate that consumers’ purchase intention for a PHYD tariff is higher for integrated price framing compared to segregated price framing. Also, we show that the amount of discount (surcharge) on the price moderates the effect of price framing on purchase intention for a PHYD tariff. Finally, we show that the sureness effect (i.e., sureness about having no unexpectedly high billing rates due to variation in driving style and mileage) mediates the effect of price framing and on purchase intention for PHYD tariff.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Car insurance; Consumer experience; Framing; Pay-how-you-drive

The psychological effects on tariff choices for car insurance - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2017)